Stealing Lincoln's body - Nelson, Troy; Courtney, Kent, Jr., 1953-; Dwyer, Thomas Daniel; Gooley, Matthew; Mantell, Ed; Moran, Luke Austin; Peddie, John; Lincoln, Abraham, 1809-1865 (New York, NY : A&E Home Video, 2009)
A gang of Chicago counterfeiters attempt to steal the tomb containing the body of Abraham Lincoln.
Kent Courtney, Thomas Daniel Dwyer, Matthew Gooley, Ed Mantell, Luke Austin Moran, John Peddie.
Originally aired as a television program on the History channel.
TV rating: Not rated.
DVD.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Tomb; Lincoln, Abraham, -- 1809-1865 -- Family; Counterfeits and counterfeiting -- United States -- History -- 19th century -- Drama; Irish American criminals -- History -- 19th century -- Drama; Grave robbing -- United States -- History -- 19th century -- Drama; Grave robbing -- Illinois -- Springfield -- History -- 19th century -- Drama; Crime and the press -- United States -- History -- 19th century -- Drama; Nonfiction films; Feature films; Historical films